Evolusi Perundang-Undangan di Era Konstitusi Hukum: Tantangan dan Peluang - Kamal Fahmi Kurnia; Rizky Mahendra; Aditnya Prayoga (IKIP Budi Utomo Malang, 2023)
The life of the legal constitution has undergone significant developments since the past to the current modern era. The legal constitution era marked a paradigm shift from absolute authority to government based on the rule of law and recognition of human rights. These changes have influenced the formation and interpretation of legislation governing the social, political and economic order in various countries. This article examines the evolution of legislation in the legal constitutional era by highlighting the challenges and opportunities faced. The main challenges stem from the complexity of the problems faced by modern society, including globalization, technology, environment and social dynamics. Rapid social change often requires a comparable legislative response to maintain justice and balance in society. In addition to challenges, the era of legal constitutions also brings opportunities for more inclusive and progressive legal innovations. By giving power to constitutional institutions such as the Constitutional Court, legislation can accommodate the aspirations and needs of diverse communities. Increasing public participation in the legislative process is also one of the great potentials for creating more representative and responsive laws. This study uses a descriptive analysis method by reviewing the latest literature on changes to the legal constitution and their impact on legislation. The main findings show that the evolution of legislation in the era of legal constitutions provides complex consequences and challenges, but at the same time presents opportunities to create a legal system that is more just and relevant to the times